A pectin-honey hydrogel prevents postoperative intraperitoneal adhesions in a rat model. Issue 1 (December 2016) - Giusto, Gessica; Vercelli, Cristina; Iussich, Selina; Audisio, Andrea; Morello, Emanuela; Odore, Rosangela; Gandini, Marco
Abstract Background Adhesions are a common postoperative surgical complication. Liquid honey has been used intraperitoneally to reduce the incidence of these adhesions. However, solid barriers are considered more effective than liquids in decreasing postoperative intra-abdominal adhesion formation; therefore, a new pectin-honey hydrogel (PHH) was produced and its effectiveness was evaluated in a rat cecal abrasion model. Standardized cecal/peritoneal abrasion was performed through laparotomy in 48 adult Sprague-Dawley rats to induce peritoneal adhesion formation. Rats were randomly assigned to a control (C) and treatment (T) group. In group T, PHHs were placed between the injured peritoneum and cecum. Animals were euthanized on day 15 after surgery. Adhesions were evaluated macroscopically and adhesion scores were recorded and compared between the two groups. Inflammation, fibrosis, and neovascularization were histologically graded and compared between the groups. Results In group C, 17 of 24 (70.8%) animals developed adhesions between the cecum and peritoneum, while in group T only 5 of 24 (20.8%) did (p  = 0.0012). In group C, one rat had an adhesion score of 3, sixteen had scores of 2, and seven rats had scores of 0. In group T, four rats had adhesion scores of 2, one rat had an adhesion score of 1 and nineteen have score 0 (p  = 0.0003). Significantly lower grades of inflammation, fibrosis, and neovascularization were seen in group T (p  = 0.006, p  = 0.001, p  = 0.002, respectively). Conclusion PHH is a novel absorbable barrier that is effective in preventing intra-abdominal adhesions in a cecal abrasion model in rats.